Influence of light availability and seed mass on germinability and initial growth of two congeneric species of Fabaceae - Fagundes, Marcilio; Cuevas-Reyes, Pablo; Araujo, Walter S.; Faria, Mauricio L.; Valerio, Henrique M.; Pimenta, Marcio A.; Falcão, Luis A.D.; Reis-Junior, Ronaldo; Aguilar-Peralta, Joan Sebastian; dos Santos, Henrique Tadeu (Instituto de Ecología, A.C., 2020)
Background and Aims: Environmental factors can interact with plant life history to determinate the reproductive strategies of adult plants and seedling recruitment. We expect that widely distributed tree species produce heavier seed and with greater variation in seed size than shrubs of restricted geographic distribution. We also predict that widely distributed tree species should be capable to germinate and develop under variable range of light conditions, while sun-adapted shrubs should germinate and develop better under high light intensity. We used as models two congeneric species of Fabaceae. Copaifera langsdorffii is a widely distributed arboreal species and C. oblongifolia is a shrub with restricted distribution. Methods: Seeds were collected from two plant species in a Cerrado vegetation area, northern Minas Gerais, Brazil. The effects of light available on seed germination and seedling development was conducted in a germination chamber with controlled photoperiod, temperature and light intensity.Key results: The widely distributed tree (C. langsdorffii) had greater seed mass than the shrub (C. oblongifolia). Seeds of C. langsdorffii germinated faster under available high light, while the shrub C. oblongifolia seeds required less time to germinate under available low light and darkness. Under high light intensity, germination percentage of C. langsdorffii and C. oblongifolia seeds did not vary. However, seeds of the shrub showed a higher germination percentage under low light intensity and darkness. In general, seed mass showed a negative relationship with germination percentage, but this relationship varied in function of species and the availability of light. Copaifera langsdorffii seedlings had larger shoots and roots than C. oblongifolia. In contrast, the root:shoot ratio was higher in shrub than in tree species.Conclusions: Our results have important implications for understanding the patterns of distribution of two Copaifera species and explain the ability of C. oblongifolia to colonize disturbed areas.